Dampak Ketidakpercayaan Masyarakat terhadap Kinerja Pemerintah Terkait Transparansi Pengalokasian Pajak Daerah Bandar Lampung - Anindya Rahma Fathiya; Janter Panjaitan; Andhika Ivan (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the impact of public distrust on government performance, especially related to the transparency of regional tax allocation in Bandar Lampung. The purpose of the study was to analyze how public perception of government transparency affects the level of tax compliance and the effectiveness of regional tax management. The methods used are literature studies and normative juridical analysis of laws and regulations as well as secondary data related to tax revenues in Bandar Lampung. The results of the study show that the lack of transparency in the management and reporting of regional taxes lowers public trust, which has an impact on low participation and compliance of taxpayers. The implications of these findings underscore the importance of increasing transparency and accountability of local governments to rebuild public trust and achieve tax revenue targets optimally.